Clinical and laboratory studies on the effects of capsular tension ring on surgical outcomes of trifocal intraocular lens implantation. Issue 4 (April 2023) - Sugita, Toru; Aomatsu, Masaru; Yoshida, Masato; Kaneko, Tsutomu; Hasegawa, Yumi; Oshika, Tetsuro
Abstract : Coimplantation of CTR did not affect refractive and visual outcomes of trifocal IOL implantation. The use of CTR significantly increased IOL decentration probably because CTR eyelets interfered with IOL haptics. Abstract : Purpose: To assess the influence of capsular tension ring (CTR) on surgical outcomes of trifocal intraocular lens (IOL) implantation in femtosecond laser-assisted cataract surgery. Setting: Sugita Eye Clinic, Tokyo, and University of Tsukuba, Ibaraki, Japan. Design: Prospective, randomized, paired-eye clinical study and laboratory study. Methods: In the clinical study involving 44 eyes of 22 patients with no risk of zonular instability, 1 eye received IOL alone and the contralateral eye received IOL with CTR. Preoperative capsular bag diameter and postoperative IOL tilt/decentration were measured using anterior segment optical coherence tomography. In the laboratory study, IOL and CTR were implanted into an artificial capsular bag of 10 mm in diameter, and IOL centration was evaluated. Results: Throughout the 12-month follow-up period, there was no significant difference in refractive and visual outcomes between groups. The amount of IOL decentration was significantly larger in eyes with CTR than in eyes without CTR at 12 months postoperatively ( P = .037). There was a significant negative correlation between capsular bag diameter and the amount of IOL decentration in eyes with CTR ( P = .038), but not in eyes without CTR ( P = .873). The laboratory study indicated that interference between CTR eyelets and IOL haptics significantly increased IOL decentration ( P < .001). Conclusions: The use of CTR did not affect refractive and visual outcomes of trifocal IOL implantation in eyes without the risk of zonular weakness. CTR coimplantation increased IOL decentration possibly due to the interference between CTR eyelets and IOL haptics.